Premenopausal osteoporosis in a patient with autoimmune polyglandular syndrome: A case report - Büşra Gürbüz; Ensar Aydemir; Coşkun Ateş; Özen Öz Gül; Yasemin Aydoğan Ünsal; Soner Cander; Erdinç Ertürk; Canan Ersoy (Turkish Journal of Internal Medicine, 2021)
Osteoporosis is a skeletal disease characterized by low bone mass associated with decreased bone strength and increased risk of fractures. Low bone mass in premenopausal women is less common than in postmenopausal women, and bone loss in premenopausal women is usually due to secondary causes such as estrogen deficiency, glucocorticoid exposure, malabsorption, thyroid disorders, and hyperparathyroidism. In women with premenopausal osteoporosis, treatment should be planned according to the underlying secondary causes. In this case report, the importance of investigating the secondary causes leading to premenopausal osteoporosis and its treatment are discussed.